LO64: A systematic review of interventions to influence opioid prescribing from the emergency department. (May 2020) - Tran, M.; Thompson, C.; Walsh, C.; McLeod, S.; Borgundvaag, B.
Abstract : Introduction: The opioid crisis has reached epidemic levels in Canada, driven in large part by prescription drug use. Emergency physicians are frequent prescribers of opioids; therefore, the emergency department (ED) represents an important setting for potential intervention to encourage rational and safe prescribing. The objective of this study was to systematically review the literature on interventions aimed to influence opioid prescribing in the ED. Methods: Electronic searches of Medline and Cochrane were conducted and reference lists were hand-searched. All quantitative studies published in English from 2009 to 2019 were eligible for inclusion. Two reviewers independently screened the search output to identify potentially eligible studies, the full texts of which were retrieved and assessed for inclusion. Outcomes of interest included opioid prescribing rate (proportion of ED visits resulting in an opioid prescription at discharge), morphine milligram equivalents per prescription and variability among prescribers. Results: The search strategy yielded 797 potentially relevant citations. After eliminating duplicate citations and studies that did not meet eligibility criteria, 34 potentially relevant studies were retrieved in full text. Of these, 28 studies were included in the review. The majority (26, 92.9%) of studies were based in the United States and two (7.1%) were from Australia. Four (14.3%) were randomized controlled trials. The interventions were classified into six categories: prescribing guidelines (n = 10), regulation/rescheduling of opioids (n = 6), prescribing data transparency (n = 4), education (n = 4), care coordination (n = 3), and electronic medical record changes (n = 1). The majority of interventions reduced the opioid prescribing rate from the ED (21/28, 75.0%), although regulation/rescheduling of opioids had mixed effectiveness, with 3/6 (50%) studies reporting a small increase in the opioid prescribing rate post-intervention. Education had small yet consistent effects on reducing the opioid prescribing rate. Conclusion: A variety of interventions have attempted to improve opioid prescribing from the ED. These interventions include prescribing guidelines, regulation/rescheduling, data transparency, education, care coordination, and electronic medical record changes. The majority of interventions reduced the opioid prescribing rate; however, regulation/rescheduling of opioids demonstrated mixed effectiveness.